2020
DOI: 10.17265/2332-7839/2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Anthropometric Indices and Lipid Profiles In-OfficeEmployees

Abstract: Purpose:The purpose of this study was to investigate the relationship between anthropometric indices and lipid profile in-office employees.Methods: This descriptive study was performed in Tehran, Iran. In total 294 office employees (166 males and 83 females) participated as samples study in this research. Blood samples (TC, TG, HDL-C, LDL-C and LDL-C to HDL-C ratio) were taken from the brachial vein in sitting position and fasting state. Then anthropometric indices includingbody mass index (BMI), waist circumf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Studies reveal the effectiveness of physical activity and regular exercise in controlling weight, balancing blood glucose level, and reducing cardiovascular risk factors (3,4,(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Iran J Health Sci 2022; 10(2): 31mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reveal the effectiveness of physical activity and regular exercise in controlling weight, balancing blood glucose level, and reducing cardiovascular risk factors (3,4,(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Iran J Health Sci 2022; 10(2): 31mentioning
confidence: 99%
“…Extensive studies have shown that obesity increases the risk of chronic diseases, such as cancer, cardiovascular disease, stroke (the leading cause of death worldwide), diabetes and its complications, and musculoskeletal disorders (e.g. osteoarthritis) (2)(3)(4)(5). Type 2 diabetes (T2D) is a metabolic disease caused by a gradual decrease in insulin secretion or the inability of the body to respond to insulin.…”
Section: Introductionmentioning
confidence: 99%